Dermatoscopy in Vitiligo: Diagnosis of the Stages - Davletshina Alina Y; Lomonosov Konstantin M (Indian Journal of Forensic Medicine & Toxicology, 2021)
The aim of the Study is to identify the main dermatoscopic patterns of vitiligo and to establish theirrelationship with the activity of the process.Materials and Methods: The study involved 63 patients with an established diagnosis of vitiligo. Therewere 34 patients with a progressive course, 11 with a stable and 18 in the repigmentation stage. All patientsunderwent dermatoscopy using a Delta 20T dermatoscope. Statistical processing of research materials wascarried out using the SPSS Statistics software package.Results. In the study, it was found that the most significant changes are manifested in the perifollicularregion. So, progressive vitiligo is characterized by perifollicular pigmentation (91.2%), an altered pigmentnetwork (97.1%), a blurred spot border (94.1%), as well as specific structures - star-shaped formations and“comet tail”. A stable vitiligo process is characterized by perifollicular depigmentation (81.8%), a sharpspot border (72.7%). For the stage of repigmentation, marginal hyperpigmentation (100%), perifolliculardepigmentation (72.2%), blurred spot border (77.8%), “pigmentation islands” (77.8%).Conclusion. For the first time, diagnostic dermatoscopic patterns of vitiligo have been developed, and theirvalue has been shown. Dermatoscopy is a promising auxiliary non-invasive tool for diagnosing vitiligo anddetermining the stage of the disease.